Change in the North Atlantic circulation associated with the mid-Pleistocene transition - G. M. Martin-Garcia; F. J. Sierro; J. A. Flores; F. Abrantes (Climate of the Past, 2018)
The southwestern Iberian margin is highly sensitive to changes in the distribution of North Atlantic currents and to the position of oceanic fronts. In this work, the evolution of oceanographic parameters from 812 to 530 ka (MIS20–MIS14) is studied based on the analysis of planktonic foraminifer assemblages from site IODP-U1385 (37°34.285′ N, 10°7.562′ W; 2585 m b.s.l.). By comparing the obtained results with published records from other North Atlantic sites between 41 and 55° N, basin-wide paleoceanographic conditions are reconstructed. Variations of assemblages dwelling in different water masses indicate a major change in the general North Atlantic circulation during MIS16, coinciding with the definite establishment of the 100 ky cyclicity associated with the mid-Pleistocene transition. At the surface, this change consisted in the redistribution of water masses, with the subsequent thermal variation, and occurred linked to the northwestward migration of the Arctic Front (AF), and the increase in the North Atlantic Deep Water (NADW) formation with respect to previous glacials. During glacials prior to MIS16, the NADW formation was very weak, which drastically slowed down the surface circulation; the AF was at a southerly position and the North Atlantic Current (NAC) diverted southeastwards, developing steep south–north, and east–west, thermal gradients and blocking the arrival of warm water, with associated moisture, to high latitudes. During MIS16, the increase in the meridional overturning circulation, in combination with the northwestward AF shift, allowed the arrival of the NAC to subpolar latitudes, multiplying the moisture availability for ice-sheet growth, which could have worked as a positive feedback to prolong the glacials towards 100 ky cycles.